Inovasi Kenyamanan dan Daya Tarik Kemasan dalam Meningkatkan Penjualan Tissue Slebew - Kukuh Hestiantoro; Sephia Indah Maharani; Elsa Fiona Andini; Juli Andrianto Prabowo; Lefi Reyinta Dwi Utomo; Diah Ayu Sanggarwati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2025)
With the rapid growth of the retail business in Indonesia, the increasing purchasing power of the people has driven product innovation to meet consumer needs. One product that has garnered attention is Tisu Slebew, offering wet and dry tissues with a focus on comfort and attractive packaging. Visually appealing packaging is a crucial component in attracting customers, creating emotional bonds, and enhancing product recall. Additionally, user convenience, such as resealable packaging features, provides a practical solution to improve consumer experience. This research aims to investigate the impact of packaging comfort and attractiveness on Tisu Slebew sales. A quantitative research method with a descriptive approach was utilized, with 96 respondents as the sample. The results indicated that an increase in packaging attractiveness had a positive impact on sales by 0.133. Comfort also had a significant positive impact on sales by 0.128. Overall, attractiveness and comfort together had a significant positive effect on Tisu Slebew sales with a value of 3.312. These findings underscore the importance of packaging design innovation and comfort in boosting retail product sales.